2004
DOI: 10.1111/j.1537-2995.2004.03283.x
|View full text |Cite
|
Sign up to set email alerts
|

Collection of two consecutive neutrophil concentrates for transfusion from donors mobilized with glycosylated granulocyte‐CSF plus dexamethasone

Abstract: Two consecutive neutrophil concentrates for transfusion can be obtained after single stimulation with Lenograstim+DXM. A second application of DXM alone is necessary, but of limited value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Lenograstim was administered at four different dosages: 789 µg (= 3 ampoules of Granocyte34, high‐dose Lenograstim group), 526 µg (= 2 ampoules of Granocyte34, intermediate‐dose lenograstim group), 263 µg (= 1 ampoule of Granocyte34, low‐dose lenograstim group), and 105 µg (= 1 ampoule of Granocyte13, very‐low‐dose lenograstim group). These regimen resulted in median lenograstim doses per kilogram of donor body weight that decreased from one group to the other by approximately 50 percent from 12 (8.2‐17.2) µg per kg lenograstim for the high‐dose group (n = 21), 6 (4.3‐7.9) µg per kg for the intermediate‐dose group (n = 123, of whom 57 had been previously reported 25 ), and 3 (2.4‐4.1) µg per kg lenograstim for the low‐dose group (n = 73, of whom 29 had been previously reported 23 ) to 1.5 (1.0‐2.3) µg per kg lenograstim for the very‐low‐dose group (n = 43). Owing to the wide variation in donor body weight, some donors with low (<60 kg) or high (>100 kg) body weight of the 1.5 µg per kg (n = 5), of the 3 µg per kg (n = 6), of the 6 µg per kg (n = 13) and of the 12 µg per kg median‐dose groups (n = 2; altogether n = 26) received lenograstim at doses that were individually adapted to their target dose and their specific body weight (e.g., the 51‐kg individual of the 3 µg/kg target dose group received 1.5 ampoules of Granocyte13).…”
Section: Donors Materials and Methodsmentioning
confidence: 91%
See 2 more Smart Citations
“…Lenograstim was administered at four different dosages: 789 µg (= 3 ampoules of Granocyte34, high‐dose Lenograstim group), 526 µg (= 2 ampoules of Granocyte34, intermediate‐dose lenograstim group), 263 µg (= 1 ampoule of Granocyte34, low‐dose lenograstim group), and 105 µg (= 1 ampoule of Granocyte13, very‐low‐dose lenograstim group). These regimen resulted in median lenograstim doses per kilogram of donor body weight that decreased from one group to the other by approximately 50 percent from 12 (8.2‐17.2) µg per kg lenograstim for the high‐dose group (n = 21), 6 (4.3‐7.9) µg per kg for the intermediate‐dose group (n = 123, of whom 57 had been previously reported 25 ), and 3 (2.4‐4.1) µg per kg lenograstim for the low‐dose group (n = 73, of whom 29 had been previously reported 23 ) to 1.5 (1.0‐2.3) µg per kg lenograstim for the very‐low‐dose group (n = 43). Owing to the wide variation in donor body weight, some donors with low (<60 kg) or high (>100 kg) body weight of the 1.5 µg per kg (n = 5), of the 3 µg per kg (n = 6), of the 6 µg per kg (n = 13) and of the 12 µg per kg median‐dose groups (n = 2; altogether n = 26) received lenograstim at doses that were individually adapted to their target dose and their specific body weight (e.g., the 51‐kg individual of the 3 µg/kg target dose group received 1.5 ampoules of Granocyte13).…”
Section: Donors Materials and Methodsmentioning
confidence: 91%
“…All NA were run on a cell separator (Spectra, COBE [now Gambro] BCT, Denver, CO) with the single‐stage WBC cytapheresis set and the PMN program of the Spectra software Version 4.7. We followed a standard procedure that has been previously described 23,25 . The NA characteristics are shown in Table 1.…”
Section: Donors Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…8 3 10 9 /L (6 lg/kg), and that dose escalation to 12 lg/kg does not improve the median PMN response (33.0 3 10 9 /L) [24]. We also demonstrated that the neutrophil mobilization capacity of LENO is so potent that neutrophil concentrates can even be collected twice, 16 and 42 h after a single dose of LENO plus DXM (LENO/DXM), with acceptable PMN yields [25].…”
Section: Introductionmentioning
confidence: 76%
“…In a previous study, we already showed that neutrophils can be collected on two consecutive occasions after stimulation with LENO (6 lg/kg) plus 8-mg DXM [25]. However, in that study, an arbitrary apheresis schedule of 16 and 40 h after mobilization was used, DXM was administered twice (the second dose 28 h after initial mobilization with LENO/DXM), and PMN yields of about 42 3 10 9 /TU were obtained.…”
mentioning
confidence: 97%